2010
DOI: 10.1111/j.1365-3180.2010.00780.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of weedy red rice (Oryza sativa) in Arkansas, USA

Abstract: Weedy red rice (Oryza sativa) is a problematic weed in cultivated rice. About 50% of US rice is produced in Arkansas and 60% of these fields have some red rice infestation. Red rice populations are morphologically and phenologically diverse. We hypothesise that red rice in Arkansas has high genetic diversity, which underlies its wide phenotypic diversity, and that some alleles from cultivated rice have been introgressed into red rice during more than a century of coexistence. We tested 137 red rice accessions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
82
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(89 citation statements)
references
References 37 publications
(63 reference statements)
5
82
1
1
Order By: Relevance
“…However, a number of valuable genes harboured in weedy rice lines such as disease resistance may seep into cultivated rice through natural hybridization and introgression (Chen et al 2004). In this study, weedy rice lines showed a relatively higher degree of GD value, similar to the results of Shivrain et al (2010). The introduced lines used here showed the highest level of GD, possibly due to their diverse geographic origins.…”
Section: Discussionsupporting
confidence: 86%
“…However, a number of valuable genes harboured in weedy rice lines such as disease resistance may seep into cultivated rice through natural hybridization and introgression (Chen et al 2004). In this study, weedy rice lines showed a relatively higher degree of GD value, similar to the results of Shivrain et al (2010). The introduced lines used here showed the highest level of GD, possibly due to their diverse geographic origins.…”
Section: Discussionsupporting
confidence: 86%
“…Whereas hull color was among the morphological traits most strongly correlated with population structure in historical U.S. weedy rice Shivrain et al, 2010a), no clear correlation between hull color and the population structure of HR weedy rice was observed (Fig. 6).…”
Section: Correlations Between Population Structure and Phenotype In Hmentioning
confidence: 90%
“…The U.S. red rice populations are genetically diverse and can be divided phenotypically and evolutionarily into two major groups: strawhull (SH; awnless) and blackhull (BH; awned) (Gealy et al 2009(Gealy et al , 2012Londo and Schaal 2007;Reagon et al 2010;Shivrain et al 2010a).…”
mentioning
confidence: 99%